2009
DOI: 10.1007/s00240-009-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigations for recognizing urinary stone

Abstract: This study was done to identify the value of the commonly performed investigations available for identifying urinary stone disease, namely X-ray of the kidney, ureter and bladder (KUB) regions and ultrasound scan (USS) to recognize stones in patients suspected to have the disease. Two hundred patients who attended the stone clinic with symptoms suggestive of urinary stone disease and had either stone retrieved or have been followed up for minimum of 6 months were interviewed. The final opinion on stone disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…A renal contrast study (Enhanced CT or Intravenous Urography) is indicated while planning treatment for a renal stone in addition to assess the function of the affected kidney. [1][2][3] Biochemical investigations like urea, electrolytes and creatinine are used to assess the renal functions whereas whole blood examination and midstream urine microscopic culture and sensitivity are used to diagnose sepsis. 4 Gamma-camera renography using I-hippuran or 99mTc-DTPA objectively analyses the accumulation, transit and elimination of injected activity by each kidney to produce the well-known time-activity curves.…”
Section: Introductionmentioning
confidence: 99%
“…A renal contrast study (Enhanced CT or Intravenous Urography) is indicated while planning treatment for a renal stone in addition to assess the function of the affected kidney. [1][2][3] Biochemical investigations like urea, electrolytes and creatinine are used to assess the renal functions whereas whole blood examination and midstream urine microscopic culture and sensitivity are used to diagnose sepsis. 4 Gamma-camera renography using I-hippuran or 99mTc-DTPA objectively analyses the accumulation, transit and elimination of injected activity by each kidney to produce the well-known time-activity curves.…”
Section: Introductionmentioning
confidence: 99%
“…Stones with a general diameter of less than 3 millimeters are difficult to find under ultrasonic examination. In the cases of our missed diagnosis, it is difficult to diagnose the echo of the stone when the patient is accompanied by chronic kidney disease or kidney atrophy (Varma et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] These diagnostic performances are also significantly better than a diagnostic approach combining KUB radiography and ultrasonography, particularly for stones less than 5 mm in size. 6,7 For these reasons, the American College of Radiology recommends unenhanced CT as the technique of choice for renal stone imaging, 9 as do the American Urological Association 10 and the European Association of Urology. 11 In France, ultrasonography is considered an acceptable first-line imaging modality according to both the French Society of Urology and the French Society of Emergency Medicine (AFU and SFMU).…”
Section: Ré Sumémentioning
confidence: 98%